Removal of Diclofenac from Aqueous Solutions Using Modified Pumice with Magnesium Chloride - Asghar Alahyari Solokloei; Mohammad Ali Baghapuor; Abooalfazl Azhdarpoor; Mohammad Reza Shirdarreh (Shiraz University of Medical Sciences, 2022)
Background:Background: Diclofenac is one of the drug compounds that is known as an emerging contaminant in aqueous solutions. Studies have shown that biological treatment is not sufficient to treat these compounds and new methods such as adsorption should be used to prevent contamination of aquatic environments. One of the native absorbers in this regard is the pumice. This study aimed to investigate the removal of diclofenac from aqueous solutions using magnesium chloride modified pumice. Methods: In this experimental study, with a practical approach, the required adsorbent was prepared from pumice. Magnesium chloride was used for pumice modification. The experiments were performed in a closed system at laboratory temperature. In this study, the effect of variables, adsorbent dose, contact time, and pH on diclofenac removal was investigated. Diclofenac was analyzed by KNAUER model HPLC at a wavelength of 254 nm. Results: Modified pumice by magnesium chloride was able to remove 95.83% of diclofenac (20 mg/l) at a concentration=1 g/l for 15 minutes at pH=5. Comparison of modified and natural pumice performance in 5, 10, 15, 30, 40 minutes with an average of 89.52% of modified pumice removal, compared to 48.15% of natural pumice removal, which was 1.86 times more efficient. Conclusion: Pumice can be used as a cheap, available, and highly effective adsorbent for the removal of diclofenac from aqueous solutions.